FORMULA AKUMULASI FACKLER UNTUK CADANGAN PREMI BERDASARKAN ASUMSI CONSTANT FORCE - Marintan Butar-butar; Hasriati '; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses Fackler accumulation formula which is used to determine reserve premium of an endowment life insurance by constant force assumption. The constant force assumption is the one that uses probability density function of exponentialdistribution. The counting of reserve premium is obtained by determining the annuity  and premium using the constant force assumption. Furthermore, an example is given to explain the problem discussed. On this case reserve premium is gotten using Fackler accumulation formula  by the constant force assumption.